Karakteristik berbagai jenis tepung ubi jalar termodifikasi dengan metode autoclaving retrogradation [Characteristics of various sweet potato flour modified by autoclaving retrogradation method] - Sefanadia Putri; Usdeka Muliani (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2021)
Sweet potato has great potency to be developed as an alternative carbohydrate source in the form of modified sweet potato flour. Autoclaving retrogradation is a physical modification method to improve the physicochemical characteristics of flour. The purpose of this study was to determine the effect of the autoclaving retrogradation method on the characteristics of various sweet potato flour: dietary fiber, resistant starch, starch digestibility, nutritional content, and antioxidant, and to determine the best modified sweet potato flour. The experimental design used a non-factorial completely randomized block design with four replications. The treatment consisted of 6 types of sweet potato, namely control (purple sweet potato without treatment), orange sweet potato, purple sweet potato, honey-sweet potato, red sweet potato, and purple white sweet potato). The results showed that there were significant differences in dietary fiber, levels of resistant starch, digestibility of starch, nutritional content, and antioxidant activity amongst various types of modified sweet potato flour. The best modified sweet potato flour was found in modified red sweet potato flour which contained 44.64% dietary fiber, 19.75% resistant starch, 13.50% starch digestibility, 66.32% antioxidant activity, with comparable nutritional content.